Devolving legislative powers : an aspect of the phenotypes of vertical separation of powers between the national and provincial level of government in the South African constitutional development - David, Soren (Stellenbosch : Stellenbosch University, 2012)
Dissertation (LL.M.) -- University of Stellenbosch, 1996.